SUCCESSFUL INSTALLATION OF ARC MELTER AT PINSTECH FOR THE SYNTHESIS OF BULK AMORPHOUS MATERIALS - Iqbal, M.; Ahmad, B. (The Nucleus, 2010)
In this paper the results on production of [Zr0.65Cu0.18Ni0.09Al0.08]98Nb2 bulk amorphous alloy synthesized by the Arc Melter WK-II are presented. The machine is installed at MSG-PD-PINSTECH for the synthesis of bulk metallic glasses (BMGs). Actually this machine is the combination of arc and induction melting furnaces with Cu mold casting facility. With the installation of this machine, it is possible to produce various types of materials locally such as bulk amorphous materials and polycrystalline materials. Both rods and sheets can be produced. The specifications of machine and procedures of materials synthesis are described. Thermal properties, crystallization behaviour and activation energy of [Zr0.65Cu0.18Ni0.09Al0.08]98Nb2 BMG have been reported. Characterization of materials was done by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) techniques. The alloy shows wide supercooled liquid region of more than 120 K. DSC results show double stage crystallization. The activation energy for first and second stage crystallization was calculated to be 198.6 and 156.7 kJ/mol. The NiZr2 (metastable phase) and CuZr2 (stable phase) were found in the annealed samples. XRD, DSC and EDS results are in good agreement.